PERCEPTIONS OF FARMERS TOWARDS AGRICULTURAL DEVELOPMENT SCHEMES OF CO-OPERATIVE BANK IN THIRUVANANTHAPURAM DISTRICT - John, Anitta (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Agriculture has the major stake to support Indian economy. A farmer is the living idol of India. Most of the people in the country are directly or indirectly involved in the agricultural sector. Co-operative banks are one of the institutions that helps and boost the farmers as well as the agriculture industry. Co-operative banks role is not limited to lending to the agriculture sector. But it expands to provide various services to the farmers. The Bank provides various government sponsored schemes and the benefits available to them under those schemes. An attempt has been made to study the perceptions of farmers towards agricultural development schemes provided by co-operative banks in Thiruvananthapuram district, with a sample size of 25 respondents. The data were collected through a structured questionnaire. A Convenient sampling method is used for the study. Both primary and secondary data were used for the study. The present study is analytical in nature.